Global gene expression profile of periodontal ligament cells submitted to mechanical loading: A systematic review - Spitz, Alice; Christovam, Ilana Oliveira; Marañón-Vásquez, Guido Artemio; Masterson, Daniele Ferreira; Adesse, Daniel; Maia, Lucianne Cople; Bolognese, Ana Maria (Archives of oral biology, 2020)
•Evidence on the global gene expression of periodontal cells under static loading is scarce.•The studies on the subject show great heterogeneity in the methods implemented.•Definitive conclusions on differentially expressed molecular pathways during orthodontic tooth movement are not yet possible. To evaluate the evidence reporting gene expression array data of human in vitro cultured periodontal ligament cells (PDLCs) submitted to static mechanical loading compared to a control group. Systematic searches were performed in MEDLINE/PubMed, Scopus, Web of Science, Virtual Health Library, The Cochrane Library and the System for Information on Grey Literature in Europe up to June 2019. A narrative synthesis was performed to summarize differentially expressed genes (DEGs). These were grouped according to the culture method (2D or 3D), force type (compression or tension) and observation time. Additionally, gene ontology (GO) analysis was performed using the Database for Annotation Visualization and Integrated Discovery. The risk of bias (RoB) and certainty of evidence (CoE) were assessed using a modified CONSORT checklist and the GRADE tool, respectively. Of eight studies included (all rated as having moderate RoB), only two provided the complete list of DEGs and four studies performed GO, gene network or pathways analysis. “Cell proliferation”, “cell-cell signaling”, “response to hypoxia and to mechanical stimulus” were among the significantly enriched biological processes in 3D-cultured compressed PDLCs (moderate CoE); while “collagen catabolic process”, “extracellular matrix organization” and “cell proliferation” were associated with DEGs of 3D-cultured PDLCs submitted to tension (very low CoE). Biological processes significantly enriched in 2D-cultured PDLCs under compression were “extracellular matrix organization”, “canonical glycolysis” and “glycolytic process” (very low CoE). Genes such as NR4A2, NR4A3, NAMPT, PGK1, and REDD1 are suggested as novel biomarkers for orthodontic tooth movement. Limited amount of evidence on the complete gene expression profile and the high heterogeneity in methodologies make it impossible to obtain definite conclusions. New studies following standardized and well-designed in vitro model and reporting complete gene expression datasets are needed.